Equity Intersections: Teachers' Experiences with Student Wellness Support During the COVID-19 Pandemic - Kate L. Phillippo; Elizabeth Levine Brown; Linda Galib; Ken A. Fujimoto; Aidyn L. Iachini; Naomi Brown; Crystal Lennix; Audra Parker; Tasha M. Childs (SAGE Publishing, 2024)
Teachers often address student wellness concerns such as health and mental health. Yet, this work goes largely unacknowledged and unsupported by professional preparation. COVID-19 intensified these concerns amid disrupted systems of student support and increased student distress. Our national survey (N = 1398) pursued the powerful opportunity present during the pandemic to understand the extent and distribution of demands on teachers to address student wellness and the support they receive for such work. We found that the demand for teachers' wellness work was inequitably distributed across teachers, varying largely by their schools' sociodemographic characteristics. Additionally, access to support for this work did not align with demand levels. We discuss these findings' implications for teacher preparation, support, and workload equity.